8x-73=3x-13

Simple and best practice solution for 8x-73=3x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-73=3x-13 equation:


Simplifying
8x + -73 = 3x + -13

Reorder the terms:
-73 + 8x = 3x + -13

Reorder the terms:
-73 + 8x = -13 + 3x

Solving
-73 + 8x = -13 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-73 + 8x + -3x = -13 + 3x + -3x

Combine like terms: 8x + -3x = 5x
-73 + 5x = -13 + 3x + -3x

Combine like terms: 3x + -3x = 0
-73 + 5x = -13 + 0
-73 + 5x = -13

Add '73' to each side of the equation.
-73 + 73 + 5x = -13 + 73

Combine like terms: -73 + 73 = 0
0 + 5x = -13 + 73
5x = -13 + 73

Combine like terms: -13 + 73 = 60
5x = 60

Divide each side by '5'.
x = 12

Simplifying
x = 12

See similar equations:

| 3x-7=7x-9 | | -11n=99 | | 2-5v-6v=2 | | 2-5v-6v=23 | | 12-7x=144-35x | | 42=-3(4n-2) | | -p-8p=3-6p | | -32=-2v | | -2a+5=5 | | 6(2x-9)=-102 | | -4n=-n-6 | | 7x^2-6= | | -39x+31=225 | | -12=-x-5x | | 8x+3=9+5x | | 6=14+n | | 3(5+3x)=-3(6-2x) | | 3x+14=x+24 | | -3x+1=-5x+17 | | 6=10-x | | 3(x+3)=(4+x) | | 2x+2x-1=12 | | 4Y+20=8 | | -3x+8=-2x+9 | | 10x-7= | | 2(2+2)*3= | | -3x-10=x-6 | | [a+5]=7 | | 4+4(2-4b)=-52 | | 2(5x+9)=-38+6 | | 3x+1x=28 | | 400w-3w=10450 |

Equations solver categories